Genetic diversity of native potatoes (Solanumspp.) conserved in landraces from Peru - Soto, Julián (2013)
This paper analyzes the genetic diversity of 79 accessions of native potato varieties (Solanum spp.) using 18 microsatellite markers. A random sample from Ayacucho, Cajamarca, Cusco, Huancavelica and Puno from "chacras" of farmers who collaborated with the "In situ conservation of native crops and wild relatives" were used. 17 markers amplified one single polymorphic locus, the mean number of alleles per locus was 8.79. The mean similarity was 0.62 and clustering indexes varied between 0.41 and 0.98. 19 loci showed a total of 166 alleles. Cuzco had the highest number of alleles (130 alleles). Of the 166 characterized alleles, 72 alleles (43.37%) were common or shared with 5 sampling sites. Puno had the highest number of exclusive alleles (8 alleles). The 42 varieties of S. tuberosum subsp. andigena showed a mean diversity of 0.74 and 18 varieties of S. x chauchaan average diversity of 0.70. Polymorphism (PIC = 0.55 to 0.85) and genetic diversity indices show that microsatellites evaluated can identify high levels of genetic diversity, but also are not sufficient to discriminate differentiated by origin or species groups. Our analyzes indicate a high genetic diversity and are consistent with inventories and morphological characterizations performed in situ, we can also conclude that there would be a common pool of genes would be found widely distributed among the regions studied.